A simple fluorene core-based non-fullerene acceptor for high performance organic solar cells. Issue 95 (15th November 2017) - Suman,; Bagui, Anirban; Datt, Ram; Gupta, Vinay; Singh, Surya Prakash
Abstract : A small molecule non-fullerene acceptor based on a fluorene core having a furan π-spacer and end capped with rhodanine (FRd2 ) is developed for solution processable bulk heterojunction organic solar cells (OSCs). Abstract : A small molecule non-fullerene acceptor based on a fluorene core having a furan π-spacer and end capped with rhodanine (FRd2 ) is developed for solution processable bulk heterojunction organic solar cells (OSCs). The simplistic synthetic protocol reduces several reaction steps and hence production cost. Extended π-conjugation via furan units and the presence of electronegative rhodanine groups result in a power conversion efficiency of 9.4% in OSCs, which is the highest so far among these categories of molecules.